A material catalogue with glass-like thermal conductivity mediated by crystallographic occupancy for thermoelectric application. Issue 6 (13th May 2021) - Liu, Zihang; Zhang, Wenhao; Gao, Weihong; Mori, Takao
Abstract : We proposed a new crystallographic parameter, namely the site occupancy factor, as an effective indicator to discover a material catalogue with low lattice thermal conductivity for thermoelectric application. Abstract : Discovering materials with intrinsically low lattice thermal conductivity κ lat is an important route for achieving high thermoelectric performance. In reality, the conventional synthetic approach, however, relies on trial and error. Herein, we proposed a new crystallographic parameter, namely the site occupancy factor, as an effective indicator to identify a material catalogue with low κ lat . Taking Cu6 Te3 S, in which some Cu atoms show partial occupancy, as the representative sample, it was found that this compound exhibited ultralow κ lat with weak temperature dependence from 5 K to 350 K. The appearance of a boson peak and unusual two-level tunneling states in the heat capacity measurement revealed the low-lying optical modes and dynamic diffusion disorder, respectively. This glass-like thermal property in a crystalline material arose from the combination of the anharmonic and anisotropic vibration of the Cu atom, the ionic bond feature around the Cu atom, and the global weak bonding, confirmed by the calculated phonon dispersion, electron localization function, and potential energy curves. Utilizing the proposed indicator of partial occupancy, we searched in the Crystallography Open Database for further potential candidate materials with low κ lat . As a further test of the efficacy of this strategy, two unearthed compounds were synthesized and both were indeed found to exhibit very low κ lat, around 0.6 W m −1 K −1 at 300 K. Our work explored the close relationship between crystallography and thermal property in crystalline materials and revealed the impact of partial occupancy in complex lattice dynamics, opening up new avenues towards discovering materials with low κ lat .